Quality of Carcass and Fat of Pigs Receiving Diets with Sorghum, Canola Expeller and Peas - Bauza Devessi, Roberto Mario; Barreto González, Roberto; Silva, Dalel; Bratschi, Cecilia (Agrociencia Uruguay, 2019)
In order to determine the effect on carcass and fat characteristics of replacing maize and soybean meal (SM) with low tannin sorghum (LTS) and canola expeller (CE), respectively, 42 pig carcasses from seven feeding systems were studied: T1, Maize/SM; T2: LTS/SM grain; T3: LTS/SM wet grain silo; T4: Maize/wet grain sorghum MT/SM silo; T5: Maize/sorghum grain MT/SM; T6: Maize/(CE/peas); T7: LTS grain/(CE/peas). The pigs were slaughtered with an average live weight of 108 ± 2 kg. Carcass length, dorsal fat thickness, loin eye area, meat/fat ratio in steak, intramuscular fat content, and lipid profile were evaluated. There were no differences between treatments in carcass characteristics. Intramuscular fat content was higher in T4 pigs. Diets with CE substituting SM presented higher content ofω3 acids. It is concluded that the replacement of maize with LTS in diets for fattening pigs does not change the composition of carcasses nor the lipid profile of the dorsal fat. The replacement of SM with a mixture of CE and peas does not affect carcass characteristics but changes the lipid profile, with an increase of ω3.